STRESS AND MENTAL DISORDERS AMONG THE ELDERLY IN EMERGING TOURISM DESTINATIONS IN BALI - Ni Ketut Sri Diniari; Marianto, Marianto (Bajang Institute, 2026)
Mental disorders, including stress, anxiety, depression, cognitive impairment, and insomnia, are highly prevalent among the elderly, affecting approximately 15% of this population. In rapidly urbanizing areas such as Nusa Penida Island, Bali, substantial transitions from agricultural communities to major tourist destinations have occurred, attracting both domestic and international visitors. These transitions may adversely affect the mental health of elderly through cultural changes, lifestyle modifications, shifts in family structures, increased population density, and frequent interactions with tourism stakeholders and tourists. This study aimed to determine the prevalence and characteristics of stress and mental disorders among the elderly population in Nusa Penida. Screening of 66 elderly individuals revealed that 63.6% experienced moderate stress, 62.1% had mild anxiety, 94.0% had mild to moderate depression, and 51.5% had moderate to severe cognitive impairment. Elder individuals with moderate stress were quite likely to experience severe anxiety, mild to moderate depression, and moderate cognitive impairment. The high prevalence of stress, anxiety, and other mental disorders among elderly individuals in newly developed tourist destinations indicates the urgent need for targeted interventions to improve their overall quality of life.